Monoclonal antibody 2C5 specifically targets neutrophil extracellular traps - Livia P. Mendes; Kobra Rostamizadeh; Kandace Gollomp; Jacob W. Myerson; Oscar A. Marcos-Contreras; Marco Zamora; Ed Luther; Jacob S. Brenner; Nina Filipczak; Xiang Li; Vladimir P. Torchilin (Taylor & Francis Group, 2020)
Neutrophils can release DNA and granular cytoplasmic proteins that form smooth filaments of stacked nucleosomes (NS). These structures, called neutrophil extracellular traps (NETs), are involved in multiple pathological processes, and NET formation and removal are clinically significant. The monoclonal antibody 2C5 has strong specificity toward intact NS but not to individual NS components, indicating that 2C5 could potentially target NS in NETs. In this study, NETs were generated in vitro using neutrophils and HL-60 cells differentiated into granulocyte-like cells. The specificity of 2C5 toward NETs was evaluated by ELISA, which showed that it binds to NETs with the specificity similar to that for purified nucleohistone substrate. Immunofluorescence showed that 2C5 stains NETs in both static and perfused microfluidic cell cultures, even after NET compaction. Modification of liposomes with 2C5 dramatically enhanced liposome association with NETs. Our results suggest that 2C5 could be used to identify and visualize NETs and serve as a ligand for NET-targeted diagnostics and therapies.